Pragnienie opowieści - Śniedziewski, Piotr (Przestrzenie Teorii, 2015)
The aim of this article is to discuss Mirosław Loba’s book titled Wokół narracyjnego zwrotu. Szkice krytyczne [Around the Narrative Turn: Critical Essays]. The book is a reconstruction of the main trends in contemporary French thought on narrative (the psychoanalytic approach and Paul Ricoeur’s concept are particularly emphasized). Loba’s theoretical perspective is complemented by analytical attempts – the researcher interprets Andrea Camilleri’s and Donna Leon’s criminal novels and he also proposes one of the most interesting Polish interpretations of Jonathan Little’s The Kindly Ones.